Community Diet Management with Diabetes Mellitus (DM) during the Pandemic - Sari, Citra Windani Mambang; Lukman, Mamat; Mulya, Adelse Prima (Media Karya Kesehatan, 2023)
The Covid 19 pandemic can cause several symptoms and even result in death. Especially for people with DM, Covid 19 tends to cause severe symptoms and other complications. Seeing the current conditions, many people are not familiar with and know about DM prevention, especially dietary management for DM sufferers during a pandemic. The aim of PPM is to increase the knowledge of the Babakan Sari Village community regarding dietary management for DM sufferers during a pandemic. The method of implementing PPM, starting from preparation to implementing health education, is carried out in a hybrid manner. Data analysis used paired samples T-test. The results of the activity showed that before health education was carried out, the average knowledge value was 75 and after it was carried out, it increased to 81.7 with a p-value of 0.00. The conclusion from this PPM is that increasing knowledge is a good start for the community in getting to know dietary management for people with DM. The implication of PPM is that it is hoped that the people who take part in this activity can also share information with the surrounding community, especially in the Babakan Sari urban village area, Bandung City and support and follow-up is needed from the Babakan Sari Health Center. Keywords: Diabetes Mellitus,  health education, diabetic diet, pandemic.